STUDI TENTANG PROSES PEMBUATAN ANYAMAN NYIRU DI NAGARI BUKIK KANDUANG KECAMATAN X KOTO DI ATAS KABUPATEN SOLOK - Yani Angraini, Minarsih, Irwan (Serupa The Journal of Art Education, 2013)
This study purpose has to describe : 1) kind of material was used to created nyiru woven, 2) tools was to created nyiru woven, 3) the material processing in created nyiru woven, 4) the thechnique and the form was used to created nyiru woven, 5) the colours and the finishing thechnique was used to created nyiru woven. This study used describe qualitative method. Data sources in the study has primary data, such as interview  statement with the craftman and secondary data such as library literature. The procedure data collection was collected by observation, interview and documentation. Data analysis performed by data reduction, data display ( data prentation ) and draw conclutions. Validity checking of the study result used triangulation thechnique.